Activation of human T cells with NK cell markers by staphylococcal enterotoxin A via IL-12 but not via IL-18 - AMI, K (Blackwell Science Inc, 2002)
We have reported recently that mouse liver NK cells and NK1·1(+) T cells were activated by bacterial superantigens via the IL-12 production from Kupffer cells. In the present study, we examined the effect of staphyloccoccal enterotoxin A (SEA) on human T cells with NK cell markers, CD56 or CD57 (NK-type T cells). After stimulating peripheral blood mononuclear cells (PBMC) with SEA, PBMC produced a large amount of IFN-γ and acquired a potent antitumour cytotoxicity. The in vitro depletion of either CD56(+) TCR(–) NK cells, CD56(+) T cells or 57(+) T cells from PBMC significantly inhibited the IFN-γ production from PBMC. When purified NK-type T cells, NK cells and regular T cells were cultured with monocytes and SEA they all produced IFN-γ, while the IFN-γ amounts produced by both NK-type T cells were greater than those produced by NK cells. NK cells as well as CD56(+) T cells showed cytotoxicity against NK-sensitive K562 cells, whereas both NK-type T cells showed a more potent cytotoxicity against NK-resistant Raji cells than did NK cells. The IFN-γ production from each population as well as from whole PBMC was greatly inhibited by anti-IL-12 antibody but not by anti-IL-18 antibody. The antitumour cytotoxicity of whole PBMC was also significantly inhibited by anti-IL-12 antibody while the SEA-induced proliferation of PBMC was not affected by anti-IL-12 antibody. Furthermore, SEA-activated NK-type T cells as well as NK cells showed cytotoxicities against vascular endothelial cells. Our findings suggest that human NK-type T cells are thus involved in bacterial superantigen-induced immune response.